A Alternância desde a Formação de Professores na Licenciatura em Educação do Campo na Universidade Federal de Mato Grosso do Sul - Brasil, Kelly Cardoso (2021)
Associated to the research line "Formative processes, educational practices, differences" of the Postgraduate Program in Education of the Federal University of Mato Grosso do Sul (UFMS), this investigation had as its general objective to analyze the alternation since the formation of teachers of the degree course in Field Education at the Federal University of Mato Grosso do Sul. The specific goals were: to analyze the documents/regulations, resolutions/laws that govern the public policies for rural education and to present, describe, and discuss the alternating cycle training in the undergraduate course in Rural Education at the Federal University of Mato Grosso do Sul - Leducampo. The research was anchored on the theoretical-methodological contribution of the cultural-historical theory, represented by Vygotsky and his interlocutors in relation to authors who study rural education and the Pedagogy of Alternating Cycle, questioning whether the alternating cycle modality has enabled access and permanence for the formation of the students of the Undergraduate Degree in Rural Education of the UFMS. To reach the research goal, we conducted a documental analysis of the Pedagogical Project of the course under discussion and carried out semistructured interviews with six students and two teachers of this degree program, highlighting the formation process in alternation. We verified that the organization of the licentiate degree in alternating cycle has been configured as an important and counter-hegemonic mechanism for the concretization of teaching formation in specific licentiates to act in rural schools. We highlight the conflicts, tensions, potentialities, and challenges faced in the realization of a higher education course, having alternating cycle as a mediator of the organization of pedagogical work and the production of knowledge socially committed to the rural working class. We understand that the alternating cycle, in the condition of theoretical and methodological strategy of didactic-pedagogical organization, reinforces the alternative so that the subjects, when attending higher education, avoid leaving the countryside, complete the course and, as graduates, integrate themselves into the rural schools in MS, in the condition of qualified teachers in a formation process that places them as subjects of law, inside the university, in their professional and personal project.